The massacre of a people : what the democracies can do - Jewish Frontier Association (New York : Jewish Frontier Association, 1942)
Bibliotheek Camille Huysmans
Dedicator: Poale Zion, dedicatee: Huysmans, Camille
Engels
Brochure
Keywords: jodenvervolging; genocide; Wereldoorlog 2